PENGARUH LEVERAGE, KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN DAN ARUS KAS OPERASI TERHADAP PERSISTENSI LABA (Studi Empiris Perusahaan Sub Sektor Perbankan dan Asuransi yang Terdaftar di Bursa Efek Indonesia (BEI) 2021-2023) - Caroline Losawene; Restu Agusti; Fitri Humairoh (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to investigate the impact of leverage, managerial ownership, company size, andoperating cash flow on earnings persistence in the banking and insurance sectors listed on theIndonesia Stock Exchange for the period 2021 to 2023. Quantitative methods were used, relyingon secondary data sourced from annual financial reports. A total of 112 research samples werecollected using purposive sampling techniques. Data processing used classical assumption testsand hypothesis testing with multiple regression techniques assisted by SPSS version 27. Theresults of the analysis show that managerial ownership and company size have a significanteffect on profit persistence. On the other hand, leverage and operating cash flow did not showany effect on profit persistence.Keywords: Leverage, Managerial Ownership, Company Size, Operating Cash Flow, ProfitPersistence